Unstable behaviour of rocks - Phong, Luong Minh (Vietnam Journal of Mechanics, 2009)
This paper aims to introduce a new non-destructive testing technique in use for detecting the occurrence of material instability and a specific data reduction procedure to access damage accumulation. An input-output non-parametric procedure based on ultrasonic pulse propagation, and a non-linear analyser were chosen to portray the unstable behaviour of brittle rock material under static compressive loading. It can be used to monitor non-destructively and continuously the overall alteration or damage process so that damage mechanisms could be quantitatively estimated by a dimensionless parameter the so-called non-linearity ratio.